Systematic Literature Review: Digital Learning Media in Supporting Students’ Mathematical Representation Skills - Putri Dewi Amelia; Ekasatya Aldila Afriansyah; Indrie Noor Aini (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The growth of digital technology has opened up new opportunities to strengthen students' mathematical representation skills, particularly through learning media that are both interactive and contextual. With this in mind, the present study seeks to examine research trends, the types of digital learning media used, the educational levels involved, and the aspects of mathematical representation that have been explored. A PRISMA-based Systematic Literature Review was conducted by examining and synthesizing evidence from 33 relevant studies published between 2016 and 2025. The findings reveal a consistent upward trend in studies examining digital learning media. GeoGebra emerges as the most dominant tool, used in 36% of the reviewed research, followed closely by digital learning materials like e-modules and e-worksheets (24%) and audiovisual media (15%). Interestingly, junior high school appears to be the most common educational level studied, with most research giving particular attention to visual representation. Research is predominantly conducted at the junior high school level, with a primary focus on visual representation. Meanwhile, verbal representations have been relatively under-studied, indicating a research gap. These findings suggest that the development of digital learning media needs to be balanced to support all aspects of students’ mathematical representation skills.